How Product Order Affects Market Identity - Kim, Bo Kyung; Jensen, Michael (Administrative Science Quarterly, 2011)
In this study, we view market identities as interfaces between organizations and their external audiences and examine how the perceived market appeal of organizations can be influenced by the order in which the products or product features that determine their market identities are offered. We theorize that when audiences have different product preferences, organizations may increase their perceived appeal to some or all audiences by making certain features more or less salient through different orderings without making substantive changes to their products or product portfolios. We find strong support for our arguments in statistical analyses of the market identities of U.S. opera companies from 1995 to 2005. When opera companies group unconventional operas together, their market appeal decreases among season-ticket holders, an audience for whom unconventional opera is less appealing, but increases among opera critics, an audience for whom unconventional opera is more appealing.